Anterior Visceral Endoderm SMAD4 Signaling Specifies Anterior Embryonic Patterning and Head Induction in Mice - Cuiling Li, Yi-Ping Li, Xin-Yuan Fu, Chu-Xia Deng (International Journal of Biological Sciences, 2010)
SMAD4 serves as a common mediator for signaling of TGF-β superfamily. Previous studies illustrated that SMAD4-null mice die at embryonic day 6.5 (E6.5) due to failure of mesoderm induction and extraembryonic defects; however, functions of SMAD4 in each germ layer remain elusive. To investigate this, we disrupted SMAD4 in the visceral endoderm and epiblast, respectively, using a Cre-loxP mediated approach. We showed that mutant embryos lack of SMAD4 in the visceral endoderm (Smad4Co/Co;TTR-Cre) died at E7.5-E9.5 without head-fold and anterior embryonic structures. We demonstrated that TGF-β regulates expression of several genes, such as Hex1, Cer1, and Lim1, in the anterior visceral endoderm (AVE), and the failure of anterior embryonic development in Smad4Co/Co;TTR-Cre embryos is accompanied by diminished expression of these genes. Consistent with this finding, SMAD4-deficient embryoid bodies showed impaired responsiveness to TGF-β-induced gene expression and morphological changes. On the other hand, embryos carrying Cre-loxP mediated disruption of SMAD4 in the epiblasts exhibited relatively normal mesoderm and head-fold induction although they all displayed profound patterning defects in the later stages of gastrulation. Cumulatively, our data indicate that SMAD4 signaling in the epiblasts is dispensable for mesoderm induction although it remains critical for head patterning, which is significantly different from SMAD4 signaling in the AVE, where it specifies anterior embryonic patterning and head induction.